6(2-4x)=6-3x

Simple and best practice solution for 6(2-4x)=6-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2-4x)=6-3x equation:


Simplifying
6(2 + -4x) = 6 + -3x
(2 * 6 + -4x * 6) = 6 + -3x
(12 + -24x) = 6 + -3x

Solving
12 + -24x = 6 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
12 + -24x + 3x = 6 + -3x + 3x

Combine like terms: -24x + 3x = -21x
12 + -21x = 6 + -3x + 3x

Combine like terms: -3x + 3x = 0
12 + -21x = 6 + 0
12 + -21x = 6

Add '-12' to each side of the equation.
12 + -12 + -21x = 6 + -12

Combine like terms: 12 + -12 = 0
0 + -21x = 6 + -12
-21x = 6 + -12

Combine like terms: 6 + -12 = -6
-21x = -6

Divide each side by '-21'.
x = 0.2857142857

Simplifying
x = 0.2857142857

See similar equations:

| -6(2x-6)=-12x-36 | | 2(x-6)=4-(x+6) | | 3x-1+4x-1=180 | | -3(x-3)=9-4x | | T=7u^2+v | | 3x-7=17456 | | u^3-5u^2-8u+48=0 | | 2n+2.5=4(x-5)-2 | | 28+64=456 | | 20=5x+5(-3x+14) | | -180=7x-6(7x-5) | | 162=-2x-7(-2x-6) | | 1.32(4x-3)=3.38x-1.52 | | -42=-2x+3(3x+14) | | -.75X=36 | | -14b=18 | | 3s-4t=8 | | -8=-6x-7(x+16) | | 6x-10+4x=14 | | =ln^2(0.05) | | w^2-12w-21=0 | | 4-3x=8x+59 | | 9x^2+7=o | | x-3sqrtx+2=0 | | 10x+(9)=8 | | 78+17+5c=180 | | z+47+42=13z+17 | | 84-5+b=180 | | c+10+48=4c-5 | | 21+46+y=180 | | y=ln(tan^2(x)) | | 3y-30+3y-29=y+46 |

Equations solver categories